Environmental Courts and Tribunals in Asia-Pacific : Best Practices, Challenges and the Way Forward - Sulistiawati, Linda Yanti, (Brill's Asian Law Series ;, 2025)
Environmental Courts and Tribunals in Asia-Pacific is an in-depth treatment of the features, best practices, challenges and future prospects for environmental courts and tribunals (ECTs) in the Asia-Pacific region. ECTs play an important role in improving environmental dispute resolution, access to environmental justice and environmental governance, but data and academic analysis on ECTs are very limited. This book fills that gap, with ten chapters authored by leading academics, judges and lawyers from multiple jurisdictions, including Australia, China, India, Indonesia, Japan, New Zealand, Pakistan, Philippines and Sri Lanka, as well as pan-Asia-Pacific and global perspectives